Direct Observation of Hierarchical Folding in Single Riboswitch Aptamers - Greenleaf, William J. (2008)
Riboswitches regulate genes through structural changes in ligand-binding RNA aptamers. Using an optical-trapping assay based on in situ transcription by a molecule of RNA polymerase, single nascent RNAs containing pbuE adenine riboswitch aptamers were unfolded and refolded. Multiple folding states were characterized using both force-extension curves and folding trajectories under constant force by measuring the molecular contour length, kinetics, and energetics with and without adenine. Distinct folding steps correlated with the formation of key secondary or tertiary structures and with ligand binding. Adenine-induced stabilization of the weakest helix in the aptamer, the mechanical switch underlying regulatory action, was observed directly. These results provide an integrated view of hierarchical folding in an aptamer, demonstrating how complex folding can be resolved into constituent parts, and supply further insights into tertiary structure formation.